(untitled) (Palíndromo, 2014)
An essay on the limits of contempo- rary curatorial practice, about control and speech strategies on the contemporary art circuits, and the possible alienation from its original object. Is it possible that such an interesting notion as the understanding of curation as co-creation (or co-produc- tion) turns to be the speech of a curatorial practice used as an instrument of its own agenda? Can curatorial work, by crossing its desirable limits, to become corrosive to the art? Structures that are necessarily born from dialogic practices, in an effort of self-sufficiency, would tend to control aesthetic poetic projects, or worse, would tend to the production of their own future objects of analysis?